GENOTOXIC AND ANTIGENOTOXIC POTENTIAL OF THE LAGENANDRA TOXICARIA DALZ. RHIZOME METHANOL EXTRACT USING ALLIUM CEPA ASSAY - B, AKARSHA; G, KRISHNAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study is to evaluate the possible genotoxic and antigenotoxic potential of Lagenandra toxicaria rhizome methanol extract using Allium cepa root tip assay. Methods: The rhizome methanol extract was prepared using Soxhlet apparatus. The A. cepa roots were treated with various concentrations of the extract at different time points and stained with aceto-orcein. The mitotic index (MI) was calculated. Results: A significant decrease in MI and increase in the percentage of clastogenicity was observed in a time- and dose-dependent manner in the roots treated with the extract at 0.2 mg/ml, 0.5 mg/ml, 1 mg/ml, 5 mg/ml, and 10 mg/ml concentration for 1, 2, and 4 h. The field emission scanning electron microscopy and Fourier-transform infrared spectroscopy revealed evident morphological and biochemical changes at 10 mg/ml treatment when compared to control for 4 h. The agarose gel electrophoresis showed loss of DNA integrity at 10 mg/ml extract for 4 h. In situ histochemical staining by Schiff’s reagent and nitroblue tetrazolium confirmed the increased lipid peroxidation and free radical generation at 4 h treatment. Subsequently, the possible antigenotoxic potential of the plant extract was explored using H2O2 standard assays. The increased percentage of H2O2 induced nuclear lesions was reduced significantly after the modulatory treatment with extract. Conclusion: The L. toxicaria rhizome methanol extract acts as an antigenotoxic agent at lower doses and at higher doses the extract induces clastogenic effects. Further studies are needed to unravel the active component in the extract that mediates the observed phenomenon in the current study.